2017
DOI: 10.5301/hipint.5000602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI, CT, Dunn 45° and Dunn 90° alpha angle measurements in femoroacetabular impingement

Abstract: The Dunn 45° radiograph yielded a significantly higher alpha angle than Dunn 90°, axial oblique MRI, and CT imaging modalities. Use of the Dunn 90° or axial oblique MRI or CT as the threshold for cam osteoplasty may result in untreated symptomatic cam FAI. The authors recommend the Dunn 45° radiograph as the most sensitive evaluation of cam morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 20 publications
1
35
1
1
Order By: Relevance
“…With respect to combinations of lateral radiographic projections, some authors have demonstrated that the use of a three-view or two-view series provides the best approach for the evaluation of a cam morphology. [12][13][14] However, it is notable that the α angle and head-neck offset measurements from these and other XR views were reported to describe no more than 50% of the overall variation of the proximal femur shape. 13 In addition, less radiation exposure and affordable care have to be taken into account.…”
Section: Lateral Viewsmentioning
confidence: 80%
See 2 more Smart Citations
“…With respect to combinations of lateral radiographic projections, some authors have demonstrated that the use of a three-view or two-view series provides the best approach for the evaluation of a cam morphology. [12][13][14] However, it is notable that the α angle and head-neck offset measurements from these and other XR views were reported to describe no more than 50% of the overall variation of the proximal femur shape. 13 In addition, less radiation exposure and affordable care have to be taken into account.…”
Section: Lateral Viewsmentioning
confidence: 80%
“…Nonetheless, relying on XR for the characterization of complex hip pathomorphologies, such as in femoroacetabular impingement (FAI), faces considerable constraints mainly related to inconsistencies in techniques, positioning, imaging quality, and reliability of reports. [9][10][11] With regard to femoral morphology, some authors have demonstrated that the use of a three-view series (AP pelvis, Dunn 45-degree view, and frog-lateral radiographs), 12 a twoview series (Meyer lateral and Dunn 90-degree views), 13 or even a one-view series (Dunn 45-degree view) 14 is adequately sensitive for the evaluation of a cam deformity. 14 In fact, the two-view series just described was reported to provide the most effective predictions of the three-dimensional (3D) shape of the proximal femur.…”
Section: Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because this image more consistently captures the area most commonly affected by cam morphology, which allows the practitioner to more consistently visualize the area of maximal deformity. 7 The modified false-profile view with the leg internally rotated 35 has consistently shown that it, too, looks at the area of the femoral neck between the 1-and 2-o'clock positions, 2 which is this area where cam lesions are most consistently located. 8 Up to 20% of patients will complain of hip pain on the contralateral side; the Dunn view has the advantage of showing the cam lesion in both hips, whereas the modified false-profile view will look at only 1 hip.…”
Section: See Related Article On Page 3060mentioning
confidence: 99%
“…Although providers should not routinely rely on advanced imaging to diagnose FAI syndrome, in select challenging clinical situations, MRI should obtain radial series to optimally evaluate the labrum and the proximal femoral morphology. 16,17 Sphericity morphology is a conceptually appealing theory to form the basis of a "normal" hip. This permits dichotomization with arbitrary choices of "abnormal" imaging findingsdelevated alpha angles, lateral centeredge angles, and version, among a few dozen others.…”
Section: See Related Article On Page 2366mentioning
confidence: 99%